ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LABA DAN NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018) - Sari Lestari; Afifudin Afifudin; M. Cholid Mawardi (Universitas Islam Malang, 2021)
The purpose of this study is to analyze the audit committee, the composition of independent commissioners and institutional ownership partially affect earnings quality, analyze the audit committee, the composition of independent commissioners and institutional ownership simultaneously affect earnings quality and analyze earnings quality affect firm value. The type of research applied in this research is research with a quantitative approach. The type of data used in this research is secondary data. The population used in this study is the annual report of manufacturing companies listed on the IDX in 2016-2018. The data analysis technique used multiple linear regression with F and t tests. Based on the results of the research and discussion that have been carried out, the following conclusions can be drawn: The audit committee, the composition of independent commissioners and institutional ownership partially affect the earnings quality of Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2018. The audit committee, the composition of independent commissioners and institutional ownership simultaneously affect the earnings quality of Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2018. Earnings quality has an effect on firm value in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2018.Keywords: audit committee, composition of independent commissioners, institutional ownership, earnings quality and firm value